Trastornos de la comunicación en personas con esclerosis múltiple e instrumentos de evaluación - Matus R, Paulina; Tapia S, Sara (Revista Hospital Clínico Universidad de Chile, 2021)
Communication is an essential part of our social participation and the need to know how to evaluate and deal with its alterations is essential when working with people with neurological pathologies such as Multiple Sclerosis (MS). Purpose: to carry out a bibliographic review and group information related to communication problems, describing useful instruments for timely evaluation in the different areas involved. Material and method: bibliographic review related to the subject. Results: People with MS can face differents communication problems (aphasia, dysarthria or cognitive communicative disorder), it is important to have the characterization of these disorders and with tools that specifically carry out a pertinent evaluation with common language among experts. Conclusions: considering the importance of communication, its disorders as a consequence of MS and the forms of evaluation are a priority when intervening with this population.